Repo Markets : Background Note - World Bank (Washington, DC, 2016)
Repo markets are an essential component of liquid Government debt markets, acting as a transmission belt between money and debt markets, as well as serving to conduct key functions for the efficient operation of debt markets. These include, among others, credit risk management, funding debt portfolios, playing the yield curve, and covering short positions and settlement fails. The hybrid nature of a repo between a collateralized loan and a full transfer of ownership makes it a very versatile instrument for a broad range of market participants with very different business models. However, this is at the same time the reason for its complexity. This note addresses the legal, structural, accounting, tax, regulatory and infrastructure factors that are decisive for repo market development. The legal and infrastructure factors that underpin repo markets functionality are evolving ones and may be different depending on the country. The perspective adopted in this note intends to provide a balanced account of both the conceptual issues in each topic and relevant country cases, with the objective of providing policy makers with analytical tools to address their country specific context.